The usage and perceived effectiveness of different recovery modalities in amateur and elite Rugby athletes. Issue 4 (June 2017) - Tavares, Francisco; Healey, Phil; Smith, Tiaki Brett; Driller, Matthew
Highlights: No differences were found for the perception of the importance of recovery between groups. Elite Rugby athletes use significantly more recovery modalities (∼8 vs 3) in comparison to amateurs. Elite Rugby athletes implemented recovery modalities more often (∼25 vs ∼6 times per week) in comparison to amateurs. Elite Rugby athletes perceived 6 out of 11 recovery modalities to be more effective in comparison to amateurs. Abstract: Background: The use of recovery modalities to help enhance recovery is popular among athletes. However, little is known about the usage of various recovery modalities and the perception of their benefit amongst different level athletes. Therefore, the purpose of this study was to compare the usage and perceptual understanding of different recovery modalities between elite and amateur Rugby athletes. Methods: Fifty-eight amateur (n = 26) and elite (n = 32) Rugby union athletes completed a questionnaire designed to determine the usage and the perception of 15 different recovery modalities. A 5-point Likert scale was used to examine the perceived importance of recovery and effectiveness of each recovery modality. The number of different recovery modalities, and the number of times each player used each recovery modality per week was also obtained through the questionnaires. The total number of times an athlete used a recovery modality was calculated by summing the number of times each recovery modality was used per week. Results: No differences were found between groups (elite: 5.0 ± 0.2; amateur: 4.9 ± 0.3) for the perceived importance of recovery to enhance performance. When comparing the effectiveness of each recovery modality, the elite group perceived active recovery, massage, pool recovery, additional sleep and stretching to be significantly (p < 0.05) more effective in comparison to the amateur group. No significant differences were found for any other recovery modality. There was a significantly greater amount of recovery modalities used and also a higher frequency of use per week in the elite group (p > 0.05). Conclusion: Although no differences were found for the perception of the importance of recovery, elite Rugby athletes used significantly more recovery modalities and implemented recovery modalities more often in comparison to amateur Rugby athletes.